Treatment for lateral patellar impingement syndrome with arthroscopic lateral patelloplasty: a bidirectional cohort study - Tianhao Wu; Shiyu Tang; Fei Wang (Journal of Orthopaedic Surgery and Research, 2017)
Abstract Background Anterior knee pain is one of the most common musculoskeletal complaints of young patients. We notice that some patients had normal femoral trochlear, medial and lateral patellar retinaculum, and special patellar morphology, which resulted in a series of symptoms in the flexion of the knee due to the impingement of the lateral articular surface of the patella with the femur. We firstly termed this pathologic process as lateral patellar impingement syndrome (LPIS). This ambispective cohort study was to explore the curative effect of arthroscopic lateral patelloplasty for early LPIS. Methods Thirty-five early LPIS patients which underwent arthroscopic lateral patelloplasty were enrolled in our study. Evaluations consisted of pre- and postoperative symptoms, physical examinations, radiographs, and questionnaires. The Lysholm score, patellar suitable angle, patellar tilt angle, and patellar lateral shift were measured with the CT scan and Merchant X-ray film. The efficacy was graded as excellent, good, fair, and poor according to the patient’s subjective evaluation. Results The patients were followed up for an average of 41.1 ± 18.6 months. The efficacy results were excellent in 6, good in 26, fair in 2, and poor in 1. There were statistical differences in pre- and postoperative Lysholm scores (80.66 ± 5.51 vs 81.91 ± 6.21) (P < 0.05). The pre- and postoperative congruence angle, patellar tilt angle, and patellar lateral shift were significantly different (P < 0.05). Conclusions Arthroscopic lateral patelloplasty is an effective and minimal-invasive method for patients with lateral patellar impingement syndrome.